2018
DOI: 10.1177/0265407518802463
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social pressure from family and friends on turnout

Abstract: Recent research about the decision to vote or abstain finds a causal effect of social networks and social pressure. Yet this literature does not examine how this social pressure is exerted and by whom. This study aims at correcting these shortcomings. Using a two-wave panel survey conducted in Canada, we distinguish between the pressure exerted by friends and the partner and between descriptive and injunctive norms. We find that most people are not subjected to strong injunctive pressure, social pressure is mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
1
15
0
1
Order By: Relevance
“…The model also controls for cohabitation status. There is a strong empirical link between cohabitation and contagious electoral behaviour between family members (Blais et al., 2019). In light of the rising divergence between political dispositions between voters based on their geographic distribution amongst areas of different levels of urbanisation (Smets and van Ham, 2013: 350), I also include a control indicating voters who reside in rural locations.…”
Section: Methodsmentioning
confidence: 99%
“…The model also controls for cohabitation status. There is a strong empirical link between cohabitation and contagious electoral behaviour between family members (Blais et al., 2019). In light of the rising divergence between political dispositions between voters based on their geographic distribution amongst areas of different levels of urbanisation (Smets and van Ham, 2013: 350), I also include a control indicating voters who reside in rural locations.…”
Section: Methodsmentioning
confidence: 99%
“…We control for the social class of the discussant, and the frequency of dyadic political discussion because we might expect that respondents would be more likely to pick up messages about approval and disapproval the more often they discuss politics together. We also include controls for dyadic social relationship as it has previously been shown that social pressures from close family members tend to be most influential (Blais et al 2019;Fieldhouse and Cutts 2020). This finding is repeated in our data as shown in Fig.…”
Section: Injunctive Norms and Shared Partisanshipmentioning
confidence: 54%
“…That is, the coefficients for both opposing and shared identification are different to the reference category, but comparing their respective effect sizes and credible intervals, the latter are more likely to be perceived to approve of the respondent voting than the former. The effects are as large, or larger than, the equivalent effects for social relationship, which appear to be a function of social distance (Blais et al 2019;Fieldhouse and Cutts 2020). Spouses and partners have a greater effect on respondents' perceptions of discussant approval of voting than other family members, which in turn matter more than friends do and so on.…”
Section: Injunctive Norms and Shared Partisanshipmentioning
confidence: 81%
See 1 more Smart Citation
“…There is also a connection to be made between our perspective and research on the impact of social pressure on turnout (Knack 1992;Schram and Sonnemans 1996;Blais et al Forthcoming). Those who vote out of social pressure implicitly conform to the norm that the good citizen should vote.…”
Section: Introductionmentioning
confidence: 95%